Uterine scar site rupture, a rare cause of secondary PPH-case report - Haider, Samana; Majida Zafar; Hadia Hina (Journal of the Pakistan Medical Association, 2025)
The case of a woman who experienced severe secondary PPH on the fifth day following a lower segment caesarean section (LSCS), which resulted in severe anaemia is presented. The first episode of Secondary PPH was managed successfully with intravenous fluids, blood transfusions and tranexamic acid. However, a few days later she had another episode of massive vaginal bleeding leading to a haemoglobin (Hb) drop of more than 4 Grams. Given a high index of suspicion for scar site rupture, the patient underwent an exploratory laparotomy, and a peripartum hysterectomy was performed. The patient remained stable during the postpartum period and was discharged home after a few days. The report highlights the importance of high index of suspicion, conducting appropriate investigations and initiating early treatment to reduce maternal morbidity. Keywords; Secondary PPH, scar site rupture, Hysterectomy.